The Influence of Self-Efficacy on Job Search Intention and Career Readiness amongst Final –Year Job - Seeking Students of the University of Fort Hare - Saul , Amanda; Dywili, M. Tutuzeli (Reshaping Sustainable Development Goals Implementation in the World: Proceeding of 7th International Conference on Business and Management Dynamics, 2021)
Graduate unemployment has become a basic economic, social and political problem facing so many provinces in South Africa. South African graduates experienced a protest, titled “hire a graduate” in 2017 which proved the fact that the country is facing a crisis in terms of having a number of graduates who are unemployed. Graduates face an increasingly competitive labour market, and many difficulties in finding employment. Individuals have become responsible for managing their own career success and tend to avoid situations (low intention) which they do not believe they can be successful (low self-efficacy), but become more positively involved (high intention) in activities that they feel (high self-efficacy) they are capable of successfully performing. The main aim of this study was to investigate the influence of self-efficacy on job search intention and career readiness among final-year job seeking students of the University of Fort Hare. The primary data was collected using self-administered questionnaire. The respondents were selected using stratified random sampling. A total of 400 questionnaires were hand delivered to respondents and 366 of them were received back. All questionnaires returned were in working order and met the required eligibility criteria for this study. This accounted for 101% of the expected sample size of n = 362. Data was therefore obtained, from the 366 self-administered questionnaires completed by respondents (where the target sample achieved 4 extra respondents from n=362 to n=366). To measure centrality of connections among chosen variables, the Pearson Correlation and multiple regression analysis were used. The results of this study supported the hypothesis that self-efficacy beliefs correlate with and predict both career readiness and job search intention.